Increasing Production Of Purple Sweet Potato (Ipomoea Batatas Poir) By Treatment Of Shimmer Fertilizer and Kaliphos - Chloe Ava Charlotte; Gunawan, Aditiya; Patrick Ontario (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The title of the research was “Increased Production of Purple Sweet Potato (Ipomoea batatas poir) with Vermicompost and Kaliphos Fertilizer Treatment”. This research was carried out for 4 months in the experimental garden of the Faculty of Agriculture, Islamic University of Riau. The purpose of this study was to determine the effect of interaction and the main effect of increasing purple sweet potato production by the treatment of vermicompost and Kaliphos fertilizer. The design used was a completely randomized factorial design consisting of two factors. The first factor was vermicompost fertilizer (K) with 4 levels: 0. 550. 1.100. 1,650 g/bundle. The second factor is Kaliphos fertilizer: 0.5. 10. 15 g/plant. Parameters observed were the number of tubers per plant (fruit), tuber weight per tuber (g), tuber weight per plant (kg), tuber production per mound (kg), harvest index, and fresh chestnut weight per plant (kg). The last observational data were analyzed statistically and continued with the BNJ follow-up test at level 5 %. The results of the study conclude that the interaction effect of vermicompost and caliphos fertilizer is significant on tuber weight per tuber, tuber weight per plant, tuber production per mound, harvest index, and fresh chestnut weight per plant. The best treatment dose was 1,650 g/mound and Kaliphos 15 g/plant (K3L3). The main effect of vermicompost fertilizer is real in all treatments. The best treatment dose is 1,650 g/mound (K3). The main effect of caliphos fertilizer is significant for all treatments. The best treatment dose is 15 g/plant (L3).